Strategy Formulation of Balek Angin Lake as an Ecotourism Attraction to Support Sintang Regency's Sustainable Development Program - Kamaludin, Kamaludin; Antonius, Antonius; Emanuel, Viktor; Nikodimus, Nikodimus; Sinaga, Markus; Setiawan, Hendra (Journal of Indonesian Tourism and Development Studies, 2020)
This study aimed to explore the strengths and challenges in formulating a strategy to support the development of the Balek Angin Lake area under the scheme of Sintang Lestari (Sintang sustainable development protocols). This research was carried out in May and June 2019, where field visits focused around the site of Balek Angin Lake located in Akcaya I and Jerora Satu Villages in Sintang subdistrict of Sintang Regency, West Kalimantan Province. This research used a descriptive-quantitative approach. The study uses questionnaires to 10 representative informants, in-depth interviews, and field observations in data collection. Data were analyzed descriptively and SWOT analyses were used to formulate the development strategy. The results of this study show some strengths supporting the development of the area as an ecotourism site, i.e. undisturbed ecosystems, well-protected fish both in quantity and species diversity, the existence of regulation protecting lakes issued by the head of local government (Sintang Regent), and the existence of local non-governmental organization whose concern in nature protection of Balek Angin lake and upstream of Jemelak River. The main challenge, however, includes the widening business area managed by local residents, such as sand mining, plantation and settlement, disposals from households leading into the lake, and the decrease of household income as the result of the decrease of the price of Sintang's primary commodities. SWOT analyses result in 2.779 : 2.203, which means a horizontal integration strategy where collaboration among different stakeholders is needed. The strategy to develop Balek Angin Lake as an ecotourism site includes the enhancement of the ecosystem through protecting the upstream-downstream area, collaboration of local community and local government through the integration of local community, local NGO, local government, funding NGO, local academia and other environment-conscious stakeholders. Keywords: Ecotourism, Sintang, strategy.